2018
DOI: 10.1016/j.apcatb.2018.05.057
|View full text |Cite
|
Sign up to set email alerts
|

Regeneration of a sulfur-poisoned methane combustion catalyst: Structural evidence of Pd4S formation

Abstract: Decomposition of PdSO4, a species responsible for the deactivation of Pd-based methane combustion catalysts, was studied using a PdSO4/Al2O3 model system. PdSO4 was observed to behave differently under different reaction conditions. The decomposition of PdSO4 under inert atmosphere probably involved only one reaction step and resulted in the formation of metallic palladium. Under H2-containing atmosphere, the decomposition of PdSO4 resulted eventually in the formation of Pd4S, which is probably one of the many… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 25 publications
2
12
0
Order By: Relevance
“…Hydrogen consumption started around 250 °C, but no sulfur release was observed with a quadrupole mass spectrometer detector before the temperature range of 400-500 °C. The result is well in line with previous observations [26]. The decomposition of sulfate combinations began, however, at about a temperature of 100 °C lower than that for the individual…”
Section: Thermal Decomposition Of Al2o3-supported Pdso4 and Al2(so4)3supporting
confidence: 92%
See 2 more Smart Citations
“…Hydrogen consumption started around 250 °C, but no sulfur release was observed with a quadrupole mass spectrometer detector before the temperature range of 400-500 °C. The result is well in line with previous observations [26]. The decomposition of sulfate combinations began, however, at about a temperature of 100 °C lower than that for the individual…”
Section: Thermal Decomposition Of Al2o3-supported Pdso4 and Al2(so4)3supporting
confidence: 92%
“…Al 2 O 3 -supported PdSO 4 decomposes at a lower temperature compared to individual supported Al 2 (SO 4 ) 3 . Hydrogen consumption started around 250 • C, but no sulfur release was observed with a quadrupole mass spectrometer detector before the temperature range of 400-500 • C. The result is well in line with previous observations [26]. The decomposition of sulfate combinations began, however, at about a temperature of 100 • C lower than that for the individual one, and the amount of Al 2 (SO 4 ) 3 in the catalyst affected this directly-the higher the Al 2 (SO 4 ) 3 content, the lower the decomposition temperature.…”
Section: Thermal Decomposition Of Al 2 O 3 -Supported Pdso 4 and Al 2supporting
confidence: 92%
See 1 more Smart Citation
“…Thus, the regenerated active Pd/PdO may form on top of less active PdSO4. It was decided to perform regeneration at 500 • C due to the threshold temperature observed by several researchers [25,29]. Simulated exhaust gas contains reducing agents such as CH 4 , CO and NO, which can be expected to decrease the decomposition temperature of the sulfur species.…”
Section: Palladium State After Regeneration Under Simulated Exhaust Gasmentioning
confidence: 99%
“…They successfully used reductive methane pulses to partially regenerate the catalyst at 550 • C; such temperature could also be achieved in a real engine, but complete regeneration was achieved at 600 • C, which requires additional thermal energy, and may cause a fuel penalty. A reason for partial regeneration of the sulfur-poisoned catalyst has been proposed in a recent study [29], where PdSO 4 has been observed to decompose under a reductive atmosphere to Pd 4 S. Hence, small quantities of sulfur will always remain in the regenerated catalyst. They concluded also that alternately reductive (rich) and oxidative (lean) pulses result in better sulfur removal in a regenerated catalyst compared to rich-only conditions.…”
Section: Introductionmentioning
confidence: 98%